P836 Prevalence of anaemia in Italian patients with inflammatory bowel disease: Preliminary results of the observational multi-centre IG-IBD study RIDART 1. (16th January 2018) - Bergamaschi, G; Giuffrida, P; Fries, W; Aronico, N; D'Incà, R; Lenti, M V; Ciacci, C; Cococcia, S; Bossa, F; Ghigliazza, G; Castiglione, F; Principi, M B; et al.
Abstract: Background: Anaemia is the most common extra-intestinal manifestation in inflammatory bowel disease (IBD). The study "Clinical burden of anaemia in inflammatory bowel disease: Role of Iron Deficiency And iron Replacement Therapy, observational study (RIDART) 1" is an independent, observational, multi-centre study, promoted by the Italian Group for the study of inflammatory bowel disease (IG-IBD) with the primary aim to define the prevalence of anaemia in an unselected population of Italian patients with IBD. Methods: 2347 unselected Italian patients with IBD were included. The follow-up of anaemic patients was extended up to six months after recruitment in order to evaluate how anaemic patients were treated and if the ECCO guidelines for the treatment of iron deficiency anaemia in IBD were correctly applied. Here we showed preliminary results describing the main features of IBD patients with anaemia in terms of demography, disease activity, anaemia pathogenesis and severity one year after starting the study. Results: Of the 2347 IBD patients included, 305 (13%) had anaemia. A higher proportion of females was identified in the anaemic group (50%) compared with the non-anaemic one (43%; p = 0.029). No difference between anaemic and non-anaemic subjects were observed as far as patient age and disease duration are concerned. In most cases (84%) anaemia was mild (Hb≥9.5 g/dl), and only 4% of patients had severe anaemia (Hb<8.0 g/dl). Hb was lower in patients with active disease and correlated significantly with CDAI in Crohn's disease ( p = 0.0182) and CAI in ulcerative colitis ( p = 0.0021). An isolated iron deficiency was responsible for 60% of anaemic cases, the remaining cases being due to anaemia of chronic disease (8%), vitamin deficiencies (4%), and various combinations of iron and/or vitamin deficiencies and inflammation (22%). Conclusions: The lower prevalence of anaemia in RIDART 1 (13%) in comparison to that reported in previous studies (39%) may be due to the fact that, in recent years, more attention is paid to anaemia in patients with IBD and both anaemia and IBD are more effectively treated than in the past. Caution, however, must be used in the interpretation of the present data since the RIDART-1 study is still under way.